Pengaruh Konsumsi Rumah Tangga Terhadap Tingkat Inflasi Di Provinsi Kalimantan Tengah: Pendekatan Uji Kausalitas Granger - Herman Fland Dakhi; Arum Widyasyari; Dede Salwa Oktavia; Hery Kristedy; Mahdalena Mahdalena; Novi Novi; Sri Wiyanti; Wahyu Prasetyo; Dicky Perwira Ompusunggu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to analyze the impact of household consumption on the inflation rate in Central Kalimantan from 2018 to 2022 using the Granger causality test approach. Data on household consumption and inflation rates in Central Kalimantan province were obtained from the Central Kalimantan Province Central Statistics Agency. The results of the Granger causality test show that there is no causal relationship between household consumption and inflation. This means that changes in household consumption do not have a statistically significant effect on changes in the inflation rate. The unit root test results also show that the two time series data are not stationary and therefore require further analysis. Overall, the increase in inflation in Central Kalimantan from 2018 to 2022 concluded that it did not provide significant pressure to reduce household consumption. However, to maintain regional economic stability in the future, an appropriate response from the regional government is still needed.